2015
DOI: 10.1017/s0029665115002645
|View full text |Cite
|
Sign up to set email alerts
|

Product shelf life evaluation of an enriched yogurt drink containing an omega-3 nanoemulsion with enhanced bioavailability

Abstract: Long chain omega-3 polyunsaturated fatty acids (LC3PUFA) have been linked to a range of health benefits, throughout the life cycle (1) . Dietary surveys indicate that LC3PUFA are currently under consumed, particularly amongst vegetarians/vegans, adult men, pregnant/breast feeding women, infants, non-fish eaters and certain ethnic groups (2)(3)(4) . New food vehicles such as micro algae oils have been developed to bridge this gap (5) .Nanoemulsions are systems with droplet sizes in range of 20 to 500 nm (6) . T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, there were significant detrimental changes in the sensory properties of yogurt when the nanoemulsion systems were used as a fortification vehicle, which may indicate the presence of volatile oxidation compounds . A further 16‐day shelf life sensory evaluation of 50% (w/w) algal oil and lecithin nanoemulsion enriched strawberry yogurt indicated that detrimental sensory changes were detected after 2 days of storage, although significant improvements to several sensory attributes were found after 16 days of refrigerated storage, which warrants further investigation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were significant detrimental changes in the sensory properties of yogurt when the nanoemulsion systems were used as a fortification vehicle, which may indicate the presence of volatile oxidation compounds . A further 16‐day shelf life sensory evaluation of 50% (w/w) algal oil and lecithin nanoemulsion enriched strawberry yogurt indicated that detrimental sensory changes were detected after 2 days of storage, although significant improvements to several sensory attributes were found after 16 days of refrigerated storage, which warrants further investigation …”
Section: Introductionmentioning
confidence: 99%
“…20 A further 16-day shelf life sensory evaluation of 50% (w/w) algal oil and lecithin nanoemulsion enriched strawberry yogurt indicated that detrimental sensory changes were detected after 2 days of storage, although significant improvements to several sensory attributes were found after 16 days of refrigerated storage, which warrants further investigation. 21 Lecithin, a zwitterionic natural emulsifier has good emulsifying properties as a result of its molecular structure, which has hydrophilic and lipophilic groups and a hydrophilic-lipophilic balance (HLB) of eight, making it well suited to the successful creation of LC 3PUFA algal oil and marine-based oil nanoemulsions. 22 Lecithin has been used successfully to create physically stable LCn3PUFA nanoemulsion systems in various previous studies 16,19,[23][24][25] and has been found to increase the oxidative stability of emulsions at the same time as maintaining physical stability.…”
Section: Introductionmentioning
confidence: 99%